(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The article examines possible ways of developing agricultural tourism in Armenia. Analysing the experience of foreign countries, shows the importance of this sphere in the solution of social and territorial problems. The possible socioeconomic effect of developing of agricultural tourism in Armenia is evaluated.